Photocurable resin with high heat distortion temperature
A UV-curable composition of highly crosslinkable acrylate monomers and oligomers addresses the need for high HDT in additive manufacturing, achieving thermal resistance suitable for electronics and automotive applications.
Patent Information
- Application Number
- JP2024534522
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-08
- Filing Date
- 2022-12-07
- Publication Date
- 2025-01-15
AI Technical Summary
Existing additive manufacturing technologies, such as stereolithography and digital light processing, are primarily focused on prototyping and lack materials with properties comparable to traditional manufacturing techniques, particularly in high-temperature applications requiring high heat deflection temperature (HDT) for parts like electronics and automotive components.
A composition comprising highly crosslinkable acrylate monomers with four or more functional groups, combined with polyether, polyester, or unsaturated polyester oligomers, and optionally urethane acrylate oligomers, is used to create UV-curable formulations that achieve high HDT, suitable for 3D printing processes like CLIP, inkjet, SLA, and DLP.
The formulations exhibit HDTs of at least 80°C, enabling the production of 3D printed parts with enhanced thermal resistance suitable for high-temperature applications.
Smart Images

Figure 2025500812000019 
Figure 2025500812000020 
Figure 2025500812000021
Abstract
Description
[Technical field]
[0001] The present disclosure relates to 3D printing, or additive manufacturing, technologies, and more particularly, the present disclosure relates to additive manufacturing technologies based on the photopolymerization of photocurable and 3D printable compositions for stereolithography (SLA), digital light processing (DLP), continuous liquid interface manufacturing (CLIP) and inkjet, and methods of using and preparing the same. [Background technology]
[0002] In the background discussion below, reference is made to certain structures and / or methods. However, the references below should not be construed as an admission that these structures and / or methods constitute prior art. Applicants expressly reserve the right to show that such structures and / or methods do not qualify as prior art.
[0003] Photocurable compositions used in additive manufacturing techniques typically contain a photoinitiator, monomers, oligomers, and additives. Upon exposure to a light source(s) of a certain wavelength, radical polymerization is initiated to harden the monomer and oligomer network.
[0004] For the past few decades, additive manufacturing techniques, such as stereolithography (SLA) and digital light processing (DLP), have been primarily focused on prototyping with limited manufacturing opportunities. In recent years, the additive manufacturing industry has been transitioning from prototyping to manufacturing, and one of the key aspects is developing advanced materials with properties that match or exceed those used in traditional manufacturing techniques such as injection molding.
[0005] Heat Deflection Temperature is a measure of resistance to deformation when subjected to a given load (e.g., 0.455 MPa or 1.8 MPa) at elevated temperatures. The test reports the temperature at which a given test bar will deflect 0.25 mm under the given load. This property is very important for 3D printed parts that require high temperature resistance, such as electronics or automotive applications. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention reports the discovery that the use of certain highly crosslinkable acrylate monomers having three or more crosslinkable functional groups, particularly four or more functional groups, in combination with polyether acrylate oligomers, polyester oligomers, unsaturated polyester oligomers, or combinations thereof, can produce formulations that provide 3D printed parts that exhibit high HDT while maintaining physical properties such as strength that make the compositions useful in high temperature applications. This effect was further observed when any of the above oligomers were used in combination with a urethane acrylate oligomer. [Means for solving the problem]
[0007] One aspect of the present technology relates to a composition comprising one or more highly crosslinkable monomers having a functionality of at least 3, for example a functionality of at least 4, and at least one elastomeric oligomer, which is a UV curable composition. The oligomer may be, for example, a polyether acrylate oligomer, a polyester oligomer, an unsaturated polyester oligomer, or a combination thereof.
[0008] In another embodiment of the present technology, the composition has a heat deflection temperature of at least 80°C, such as at least 100°C, in particular at least 150°C.
[0009] In another embodiment of the present technology, the UV curable composition contains ethoxylated pentaerythritol tetraacrylate (PPTTA) as a highly crosslinkable monomer and an oligomer including a polyether acrylate oligomer, a polyester oligomer, an unsaturated polyester oligomer, or a combination thereof. In one embodiment, the polyether acrylate oligomer, the polyester oligomer, or the unsaturated polyester oligomer may be used in combination with a urethane acrylate oligomer.
[0010] In any embodiment, the composition can be useful for CLIP, inkjet, SLA, and / or DLP 3D printing.In any embodiment, the composition can include one or more photoinitiators.The present technology also provides a package comprising any of the compositions described herein.
[0011] In another aspect, the present technology relates to a method of manufacturing a 3D article using a composition described in any of the embodiments herein, the method comprising applying one or more successive layers of the composition described herein in any of the embodiments to create a 3D article, and exposing the successive layers to UV radiation. In any of the embodiments, the composition can be 3D printed by inkjet, CLIP, SLA, and / or DLP. These successive layers have a thickness of 50 to 200 μm. Thicker layers allow faster printing, and thinner layers provide better resolution.
[0012] In yet another related aspect, the present technology provides a 3D article comprising a UV-cured continuous layer of any of the compositions described herein. In any embodiment, the composition is deposited by inkjet, CLIP, SLA, or DLP. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 1A shows the HDT for various oligomers described in Example 3. [Figure 1B] FIG. 1B shows the tensile strength for various oligomers described in Example 3. [Figure 1C] FIG. 1C shows the E-modulus for various oligomers described in Example 3. [Figure 1D] FIG. 1D shows the elongation percentage at break for the various oligomers described in Example 3. [Diagram 2] FIG. 2 shows the HDT versus the amount of L13 as described in Example 2b. [Diagram 3] FIG. 3 shows the HDT versus the amount of L14 as described in Example 2c. [Figure 4] FIG. 4 shows the HDT versus the amount of L16 as described in Example 2d. [Diagram 5] FIG. 5 shows the HDT versus the amount of L18 as described in Example 2e. [Figure 6] FIG. 6 shows the HDT versus the amount of L21 described in Example 2f. [Figure 7] FIG. 7 shows the HDT versus the amount of L22 described in Example 2g. [Figure 8] FIG. 8 shows the HDT versus the amount of oligomer described in Example 3. [Figure 9A] FIG. 9A shows the predicted profiler results for several formulations described in Example 4. [Figure 9B] FIG. 9B shows the predicted profiler results for several formulations described in Example 4. [Figure 9C] FIG. 9C shows the predicted profiler results for several formulations described in Example 4. [Figure 9D] FIG. 9D shows predicted profiler results for several formulations described in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] definition Before describing the present invention in further detail, the terms used in this application are defined as follows, unless otherwise indicated.
[0015] As used herein, "about" will be understood by those of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If there are uses of the term that are not clear to persons of ordinary skill in the art given the context in which it is used, "about" will mean up to plus or minus 10% of the particular term.
[0016] The use of the terms "a" and "an" and "the" and similar references in the context of describing elements (particularly in the context of the claims below) should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each individual value falling within the range, unless otherwise indicated herein, and each individual value is incorporated herein as if set forth individually herein. All methods described herein may be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of all examples or exemplary language (e.g., "such as") provided herein is intended merely to better clarify the embodiments and does not limit the scope of the claims, unless otherwise indicated. No language in this specification should be construed as indicating any non-claimed element as required.
[0017] "Optional" or "optionally" means that the subsequently described circumstance may or may not occur, and the description includes cases where the circumstance occurs and cases where it does not occur.
[0018] The term "predetermined" refers to an element whose identity is known prior to its use.
[0019] As used herein, the term "stereolithography" or "SLA" refers to a form of 3D printing technology used to create models, prototypes, patterns, and parts in a layer-by-layer manner using photopolymerization, whereby light causes molecular chains to bond together to form polymers that then compose a three-dimensional solid body.
[0020] As used herein, the term "digital light processing" or "DLP" refers to an additive manufacturing process similar to stereolithography, also known as 3D printing, that takes designs created in 3D modeling software and prints 3D objects using DLP technology. DLP is a display device based on optical microelectromechanical technology that uses digital micromirror devices. DLP can be used as a light source in a printer to harden resin into a solid 3D object.
[0021] The term "heat deflection temperature" or "HDT" as used herein is a measure of a polymer's resistance to deformation under a given load at elevated temperature. In other words, it is the temperature at which a test bar of a given polymer will deflect 0.25 mm under a given load. This heat deflection temperature is also known as the "deflection temperature under load" or "heat distortion temperature." It is tested according to ASTM D648.
[0022] Detailed Description of the Invention Before describing the present invention in more detail, it is to be understood that this invention is not limited to particular embodiments described, which may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting, since the scope of the present invention will be limited only by the appended claims.
[0023] Where a range of values is provided, it is understood that each intervening value at the upper and lower limits of that range, to the tenth of the unit of the lower limit, and any other stated or intervening value in that stated range, is encompassed within the invention, unless the context clearly dictates otherwise. The upper and lower limits of these smaller ranges may independently be included in the smaller ranges and are also encompassed within the invention, subject to any specifically excluded limit in the stated range. Where the stated range includes one or both of the limits, ranges excluding either or both of those included limits are also included in the invention.
[0024] Certain ranges herein are presented by numerical values preceded by the term "about." The term "about" is used herein to provide literal support for the exact number it precedes, as well as a number that is near or approximately the number preceded by the term. In determining whether a number is near or approximately a specifically recited number, the near or approximately unrecited number may be a number that, in the context in which it is presented, provides a substantial equivalent to the specifically recited number.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, representative exemplary methods and materials are described herein.
[0026] As will be apparent to one of ordinary skill in the art reading this disclosure, each of the individual embodiments described and illustrated herein has distinct components and features which may be readily separated or combined with the features of any of the other several embodiments without departing from the scope or spirit of the invention. Any recited method can be carried out in the order of events recited or in any other order which is logically possible.
[0027] Disclosed are compositions for use in three-dimensional printing by photopolymerization.
[0028] In one embodiment, the highly crosslinkable acrylate monomer has formula I [ka] is an acrylate monomer according to wherein R1 is a branched or linear hydrocarbon chain having carbon, ether, ester or urethane linkages; R2, R3, R4, R5, R6 and R7 are independently -H or -CH3; each of X1, X2, X3, X4, X5 and X6 is independently an acrylate moiety; each of m, n, o, p, q and r is independently 0, 1, 2, 3, 4 or 5, the sum of m, n, o, p, q and r is a value from 0 to 6, preferably 3 to 5; and each of p1, p2, p3, p4, p5 and p6 is independently 0 or 1, the sum of p1 through p6 is a value from 3 to 6, for example 3 or 4, 4 to 6, or 4 or 5.
[0029] In the photopolymerizable 3D printing compositions disclosed herein, the highly crosslinkable monomers are used in combination with polyether acrylate oligomers, polyester oligomers, unsaturated polyester oligomers, or combinations thereof. These oligomers may be combined with one or more urethane acrylate oligomers.
[0030] Suitable polyether acrylates can be made, for example, from 50-75% by weight of polyether polyols, 20-50% by weight of acrylic acid, and 5% by weight of customary auxiliaries. The terms "unsaturated polyester resin", "vinyl ether" and "α-olefinically unsaturated polycarboxylic acids or their mono- or diesters" are understood below to always include mixtures of different unsaturated polyester resins, mixtures of different vinyl ethers, and mixtures of different α-olefinically unsaturated polycarboxylic acids or their mono- or diesters, respectively.
[0031] The unsaturated polyester resins a) are polyesters of polycarboxylic acids, preferably dicarboxylic acids, and polyols, preferably diols, where the use of at least one α-olefinically unsaturated polycarboxylic acid as synthesis component is essential.Possible α-olefinically unsaturated polycarboxylic acids include more specifically maleic acid, fumaric acid, itaconic acid, mesaconic acid, citraconic acid, and in the esterification, where possible, the compounds may also be used as anhydrides.Particularly preferred is maleic acid, which is more specifically also used as maleic anhydride.
[0032] In addition to the α-olefinically unsaturated polycarboxylic acid, the unsaturated polyester resin may contain further polycarboxylic acids and / or derivatives thereof, such as anhydrides or esters with low molecular weight monoalcohols, as synthetic components. Examples include ortho-phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid, hexahydrophthalic acid, methylhexahydrophthalic acid, endomethylene-hexahydrophthalic acid, dicyclopentanedicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, dodecanedicarboxylic acid, dimer fatty acid, resin acid adducts with acrylic acid or maleic acid, and mixtures of these polycarboxylic acids.
[0033] Reaction partners of the polycarboxylic acids are polyols, preferably diols, such as ethylene glycol, propylene glycol, propane-1,3-diol, 2-methylpropane-1,3-diol, butane-1,4-diol, neopentyl glycol, ethylbutylpropanediol and other so-called neo-diols (dialkylpropane-1,3-diols, alkylphenylpropane-1,3-diols), hydroxypivalic acid neopentyl glycol ester (HPN), pentane-1,5-diol, 2,2,4-trimethylpentane-1,3-diol, hexane-1,6-diol, trimethylhexanediol, dimer diol, dimethylolcyclohexane, dimethyloltricyclodecane, perhydrobisphenol A, ethoxylated bisphenol A. However, it is also possible to use more highly polyfunctional polyols, such as glycerol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, trishydroxyethyl isocyanurate.
[0034] Unsaturated polyesters may also contain monocarboxylic acids as synthetic components. These components are located at the chain ends since only one esterification is possible. More specifically, 2-ethylhexanoic acid, isononanoic acid, isodecanoic acid, and other monocarboxylic acids synthetically prepared by the Koch or Oxo process, pelargonic acid, coconut fatty acid, palm kernel fatty acid and distillate fractions of tallow, or other unsaturated fatty acids are mentioned. Monocarboxylic acids are usually used in combination with more highly multifunctional polyols. Mixtures can also be used. In particular, a specific example is the use of glycidyl esters of saturated monocarboxylic acids, in which case the glycidyl ester groups allow subsequent further reactions and the addition of further compounds. Unsaturated polyester resins may also contain hydroxycarboxylic acids and / or derivatives thereof, such as hydroxypivalic acid, dimethylolpropanoic acid, delta-valerolactone, epsilon-caprolactone, hydroxystearic acid.
[0035] The unsaturated polyester preferably has an acid value of 0 to 40, preferably 10 to 35 mgKOH / g, and a number average molecular weight of preferably 450 to 8000, more preferably 800 to 3000 g / mol. The equivalent mass based on the molar fraction of α-olefinic double bonds is preferably 170 to 1100, more preferably 200 to 800 g / mol, and based on the amount of α-olefinic double bonds, the equivalent mass gives the mass amount of α-olefinically unsaturated polycarboxylic acid present in the polyester per mole of unsaturated polyester.
[0036] The unsaturated polyesters can be prepared by conventional processes described in the literature.
[0037] In another aspect of the present technology, in addition to the highly crosslinkable monomers and elastomeric oligomers described above, the composition may have one or more dyes, pigments, or colorants. For example, such dyes, pigments, or colorants may be used to provide color or to avoid discoloration and / or aging of the printed parts that may occur during printing. Exemplary dyes, pigments, or colorants include carbon black pigments, white pigments, and various dyes such as cyan, magenta, yellow, etc. In particular, the composition includes carbon black in an amount of, for example, 0.005-0.1 wt.%, such as 0.01-0.1 wt.%, particularly 0.01-0.05 wt.%, based on the total weight of the composition. In the formulation containing the pigment, one or more dispersants may be used. Such dispersants will be known to those skilled in the art. For example, it would be possible to use EFKA4701. The dispersant may be used in an amount of about 10-100 ppm, such as 20-50 ppm, particularly 20 ppm, based on the weight of the total composition.
[0038] The composition may include one or more photoinitiators. Suitable photoinitiators include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphinate, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, alpha-hydroxycyclohexyl phenyl ketone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl-2-methylpropan-1-one, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)propanone, oligomers, and the like. Examples of photoinitiators include, but are not limited to, (2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propanone, 2-hydroxy-2-methyl-1-(4-dodecylphenyl)propanone, 2-hydroxy-2-methyl-1-[(2-hydroxyethoxy)phenyl]propanone, benzophenone, substituted benzophenones, and mixtures of any two or more thereof. In any embodiment, the one or more photoinitiators can be diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate, 1-hydroxycyclohexyl phenyl ketone, and combinations of two or more thereof.
[0039] It has been unexpectedly discovered that formulations including highly cross-linkable monomers, such as pentaerythritol tetraacrylate, and unsaturated polyester oligomers provide compositions that exhibit high HDT after photopolymerization. These compositions can be used in three-dimensional printing to provide printed parts that exhibit high HDT.
[0040] The HDT of the composition after photopolymerization may be about 80° C. or greater, about 100° C. or greater, about 150° C. or greater, or about 200° C. or greater.
[0041] A three-dimensional article formed from the composition may have a HDT of about 80° C. or greater, about 100° C. or greater, about 150° C. or greater, or about 200° C. or greater.
[0042] The weight ratio of highly crosslinkable monomer to unsaturated polyester oligomer can be about 0.3:0.7 or more, about 0.4:0.6 or more, about 0.5:0.5 or more, about 0.6:0.4 or less, about 0.7:0.3 or less, or any value encompassed by these endpoints.
[0043] The weight percentage of the ethoxylated pentaerythritol tetraacrylate may be about 20% to about 60% by weight, the weight percentage of the unsaturated polyester oligomer may be about 25% to about 75% by weight, and the weight percentage of the urethane acrylate oligomer may be about 10% to about 50% by weight, based on the total weight of the ethoxylated pentaerythritol tetraacrylate and the oligomer combined.
[0044] According to an optional embodiment, the composition further comprises an additional oligomer, which can further improve the mechanical and chemical properties of the composition of the present technology.Suitable additional oligomers include, but are not limited to, urethane acrylate, epoxy, ethoxylated or propoxylated epoxy resin, polyester, polyether, polyketone, and mixtures of two or more thereof.
[0045] Surprisingly, it has been found that the addition of a urethane acrylate oligomer to a composition containing a highly crosslinkable monomer, such as pentaerythritol tetraacrylate and an unsaturated polyester oligomer, results in a composition that exhibits a high HDT after photopolymerization.
[0046] In one embodiment, the urethane acrylate oligomer has formula (III): [ka] It is a urethane (meth)acrylate.
[0047] In the above formula, R 1is a divalent alkylene group having 2 to 12 carbon atoms and optionally substituted by a C1 to C4 alkyl group and / or interrupted by one or more oxygen atoms, said group having in particular 2 to 10 carbon atoms, more in particular 2 to 8, and very in particular 3 to 6 carbon atoms; R 2 is in each occurrence independently of the other methyl or hydrogen, particularly hydrogen; R 3 is a divalent alkylene group having 1 to 12 carbon atoms and optionally substituted with a C1 to C4 alkyl group and / or interrupted by one or more oxygen atoms, said group having particularly 2 to 10, more particularly 3 to 8, and very particularly 3 to 4 carbon atoms, and n and m are, independently of one another, positive numbers from 1 to 5, particularly 2 to 5, more particularly 2 to 4, very particularly 2 to 3, and more particularly 2 to 2.5, where R 4 is a divalent organic group formed by elimination of both isocyanate groups from an aliphatic, cycloaliphatic, or aromatic diisocyanate. Methods for the preparation of such urethane acrylate oligomers can be found, for example, in US 2016 / 0107987, the contents of which are incorporated herein by reference.
[0048] In one embodiment, the weight ratio of ethoxylated pentaerythritol tetraacrylate to unsaturated polyester oligomer may range from 0.2:0.8 to 0.8:0.2.
[0049] In one embodiment, the weight ratio of ethoxylated pentaerythritol tetraacrylate to unsaturated polyester oligomer to urethane acrylate oligomer may range from 0.2:0.05:0.75 to 0.6:0.15:0.25, and preferably 0.4:0.1:0.5, or 0.3:0.3:0.4.
[0050] In any embodiment, the one or more photoinitiators may be present in an amount of about 0.01% to about 6.0% by weight of the total weight of the composition. Suitable amounts of photoinitiators include, but are not limited to, about 0.01% to about 6.0% by weight, about 0.1% to about 4.0% by weight, about 0.20% to about 3.0% by weight, or about 0.5% to about 1.0% by weight, or about 1 to 2% by weight, based on the photopolymerizable composition. In one embodiment, the photoinitiator is present in an amount of 0.25% to about 2.0% by weight. In another embodiment, the photoinitiator is present in an amount of 0.5% to about 1.0% by weight.
[0051] According to an optional embodiment, a solvent can be used to wash the 3D printed part after printing to remove any residual uncured resin from the surface. Suitable solvents include, but are not limited to, propylene glycol monomethyl ether acetate, tripropylene glycol methyl ether, tripropylene glycol n-butyl ether, propylene glycol methyl ether, propylene glycol phenyl ether, propylene glycol n-butyl ether, propylene glycol diacetate, dipropylene glycol methyl ether, dipropylene glycol n-propyl ether, dipropylene glycol n-butyl ether, dipropylene glycol dimethyl ether, isopropanol, and mixtures of two or more thereof, as well as mixtures thereof with water.
[0052] Applying the composition to obtain a three-dimensional article may include depositing the composition. In any embodiment, applying may include depositing a first layer of the composition, depositing a second layer of the composition on the first layer, followed by depositing successive layers to obtain a 3D article. Such deposition may include one or more methods including, but not limited to, UV inkjet printing, SLA, continuous liquid interface manufacturing (CLIP), and DLP. Other applications of the composition include, but are not limited to, other coating and ink applications for printing, packaging, automotive, furniture, fiber optics, and electronics.
[0053] The methods described herein include contacting a layer of the composition with ultraviolet radiation to induce curing of the composition. In any embodiment, the contacting includes short and long wavelength ultraviolet radiation. Suitable short wavelength ultraviolet radiation includes UV-C or UV-B radiation. In one embodiment, the short wavelength ultraviolet radiation is UV-C light. Suitable long wavelength ultraviolet radiation includes UV-A radiation. Additionally, electron beam (EB) radiation may be used to induce curing of the composition.
[0054] The method described herein includes repeating the deposition of a layer of composition and exposure to UV radiation to obtain a 3D article.In any embodiment, the repeating can be performed consecutively, where the deposition of a layer of composition is repeated before exposure to UV radiation to obtain a 3D article.In any embodiment, the repeating can be performed consecutively, where the deposition of a layer of composition and exposure to UV radiation is repeated after both steps.
[0055] In another related aspect, there is provided a 3D article comprising a continuous UV-cured layer of any of the compositions described herein. In any embodiment, the composition may be inkjet, SLA, or DLP deposited.
[0056] In any embodiment, the 3D article may include a polishing pad or similar post-processing technology. In any embodiment, the polishing pad is a chemical mechanical polishing (CMP) pad. The polishing pad may be made according to any known method, for example, the method provided in US Patent Application No. 2016 / 0107381, US Patent Application No. 2016 / 0101500, and US Patent No. 10,029,405 (each of which is incorporated herein by reference).
[0057] The technology thus generally described will be more readily understood by reference to the following examples, which are provided by way of illustration and are not intended to limit the invention. EXAMPLES
[0058] All parts were measured using an Origin printer (fixed wavelength: 385 nm) at 8.5 mW / cm 2 The laser was printed at an intensity of 1000 nm. Calibration was performed between different Origin printers to ensure consistent laser intensity between different printers. After printing, the printed parts were post-treated by first removing them from the build platform, then cleaning the printed parts with 99% isopropanol, followed by sonication for 2 min in a 99% isopropanol bath at room temperature to remove any residual photoresin. The printed parts were then air-dried and cured in a UV curing box (Creative CAD Works, Professional Curezone, UV wavelength 390-410 nm and intensity 25 mW / cm). 2 ) and post-cured for 2 minutes on each side.
[0059] Tensile tests were performed according to ASTM D638 using an Instron 5965 universal testing system with a vertically 3D printed tensile bar.
[0060] Heat Deflection Temperature (HDT) measurements were performed using a Tinius Olsen HDT and VICAT Tester3Station, model 303HDTM, with a vertically oriented 3D printed HDT bar according to ASTM D648. All samples were measured at a load of 0.455 MPa.
[0061] Throughout the following examples, great care has been taken to ensure that the tests are performed using the same methods and materials, however, the printers used in performing the following tests are subject to human and uncontrollable variability, which results in some discrepancies in the data presented.
[0062] Example 1: Raw Material Screening In the following sections, the following abbreviations have the following meanings: M1 is ethoxylated pentaerythritol tetraacrylate (PPTTA), O1 is urethane acrylate oligomer (UA9089). Raw material screening tests were performed. To screen the raw materials, formulations were prepared with a mass ratio of M1:O1:selected oligomer of 40:10:50. All formulations further contained 1 wt% TPO photoinitiator. A detailed description of each oligomer is provided in Table 1.
[0063] [Table 1]
[0064] Additional results are shown in Table 2.
[0065] [Table 2]
[0066] The results shown in Tables 1 and 2 are depicted graphically in Figures 1A, 1B, 1C and 1D.
[0067] Example 2a: Ladder test From the results of the previous examples, several raw materials were identified as candidates for further evaluation in ladder testing. In particular, three formulations were prepared and tested, varying the amount of M1 and selected oligomers. The general formulations are shown in Table 3.
[0068] [Table 3]
[0069] Example 2b: Ladder test with L13 The ladder test results for the formulations containing L13 are shown in Table 4. All L13 formulations showed low tensile strength and elongation. Formulation 2 showed the lowest HDT of the three formulations with an average HDT of 73.7°C. Formulation 3 showed the highest HDT of the three formulations with an average HDT of 85°C. All of this is shown graphically in Figure 2.
[0070] [Table 4]
[0071] Example 2c: Ladder test with L14 The ladder test results for the formulations containing L14 are shown in Table 5. Increasing the L14 level from 25% to 75% by weight resulted in a slight increase in the average HDT (86.57°C to 90.47°C) and elongation (2.26% to 3.55%). The E-modulus for each of the three formulations was approximately 2000 MPa. The average tensile strength for formulation 1 was 35 MPa, increasing to 56 MPa for formulations 2 and 3. The effect on HDT as a function of the amount of L14 is shown graphically in Figure 3.
[0072] [Table 5]
[0073] Example 2d: Ladder test using L16 The ladder test results for the formulations containing L16 are shown in Table 6. Increasing the amount of L16 moderately increased the elongation and E-modulus, and tensile strength improved by 38% when comparing the formulation containing 75% L16 by weight with the formulation containing 25% L16 by weight. As shown in Figure 4, a significant increase in HDT was observed when the amount of L16 was increased from 25% to 75% by weight. Formulation 1 showed an average HDT of 75°C, Formulation 2 showed an average HDT of 90°C, and Formulation 3 showed an average HDT of 99°C.
[0074] [Table 6]
[0075] Example 2e: Ladder test with L18 The ladder test results of the formulations containing L18 are shown in Table 7. Increasing the amount of L18 decreased the elongation and increased the E-modulus. The effect on tensile strength was limited, with formulation 2 showing the highest average tensile strength (39.84 MPa). The amount of L18 made a significant difference in HDT. Formulation 1 showed an average HDT of 177.67°C with a standard deviation of 14.57°C. Formulations 2 and 3 showed much lower HDT of 99.73 and 108.33, respectively, as shown in Figure 5.
[0076] [Table 7]
[0077] Example 2f: Ladder test using L21 The ladder test results of the formulations containing L21 are shown in Table 8. Increasing the amount of L21 decreased the elongation and tensile strength. The effect on E-modulus was limited, with formulation 2 showing the highest average E-modulus (2269.65 MPa). As shown in Figure 6, formulation 1 showed an average HDT of 150°C, formulation 2 showed an average HDT of 160°C with a high standard deviation (37°C), and formulation 3 showed an average HDT of 97°C.
[0078] [Table 8]
[0079] Example 2g: Ladder test using L22 Ladder test results for formulations containing L22 are shown in Table 9. Varying the levels of L22 did not result in significant changes in HDT (shown in Figure 7), elongation, E-modulus or tensile strength.
[0080] [Table 9]
[0081] Example 3: Ladder test with three-component formulation The formulations selected from the raw material screening test for further testing were M1, O1 and L21. Therefore, additional ladder tests were conducted using these three components. The ratio of M1 to O1 was fixed at 4:1, and the amount of L21 was increased from 25% to 75% by weight. The specific formulations are shown in Table 10.
[0082] [Table 10]
[0083] The formulations were subjected to ladder testing and the results are shown in Table 11.
[0084] [Table 11]
[0085] As shown above, ladder test results for formulations containing M1, O1, and L21 show that increasing the amount of L21 increases the tensile strength. All three formulations showed relatively high HDT. Formulation 2 showed the best overall performance with HDT of 201.67±26.79°C, elongation of 3.68±0.68%, E-modulus of 2249.3±68.05MPa, and tensile strength of 65.13±9.73MPa. Formulations 1 and 3 showed average HDT of 132°C and 140°C, respectively.
[0086] Formulation 2 showed the highest HDT of all formulations tested, however this formulation showed a large variability in HDT, likely due to defects during printing. Formulation 3 also showed a relatively high HDT with an average of 140°C. In addition, the standard deviation of HDT was very small at 5.19°C, indicating improved reproducibility. The change in HDT as a function of oligomer amount is shown graphically in Figure 8.
[0087] Example 4: Formulation optimization Based on the above results and the raw material screening and ladder testing, M1, O1, L4, L18, L20 and L21 were selected for further evaluation. Of these formulations, 34 were identified as having an average HDT greater than 90° C. (all formulations except for numbers 18, 21, 26, 27, 28, 32, 33 and 42). An additional 26 formulations (except for numbers 7, 10, 18, 20, 21, 24, 25, 26, 27, 28, 30, 32, 33, 34, 41 and 42) were identified as having an average HDT greater than 100° C. Fifteen formulations (all formulations except for numbers 1, 2, 4, 5, 7, 10, 13, 15, 18, 19, 20, 21, 22, 24, 25, 26, 27, 28, 29, 30, 32, 33, 34, 37, 39, 41, and 42) were identified as having an average HDT greater than 120° C. Four formulations (numbers 6, 12, 17, and 23) were identified as having an average HDT greater than 150° C. Finally, one formulation (number 6) exhibited an average HDT of 203° C. The predictive profiler results are shown graphically in Figures 9A, 9B, 9C, and 9D.
[0088] [Table 12]
[0089] [Table 13]
[0090] Example 5: Formulation Testing Due to the DOE results, four formulations were added for testing as shown in Table 14.
[0091] [Table 14]
[0092] [Table 15]
[0093] Preferred embodiments of the invention are described herein, including the best mode known to the inventors for carrying out the invention. It will be understood that the invention is not limited to the details described above with reference to the preferred embodiments, and that numerous modifications and variations can be made without departing from the spirit and scope of the invention as defined by the following claims.
Claims
1. at least one highly crosslinkable acrylate monomer having a functionality of 3 or more; At least one of a polyether acrylate oligomer, a polyester oligomer, an unsaturated polyester oligomer, or a combination thereof; At least one photoinitiator; 1. A photopolymerizable composition comprising:
2. The at least one highly crosslinkable acrylate monomer is represented by Formula I 【Chemistry 1】 is an acrylate monomer according to In the formula, R 1 is a branched or linear hydrocarbon chain having carbon, ether, ester or urethane bonds; R 2 , R 3 , R 4 , R 5 , R 6 and R 7 are independently -H or -CH 3 And X 1 , X 2 , X 3 , X 4 , X 5 , and X 6 is independently an acrylate moiety; each of m, n, o, p, q, and r is independently 0, 1, 2, 3, 4, or 5; the sum of m, n, o, p, q, and r is a value from 3 to 5; and p 1 , p 2 , p 3 , p 4 , p 5 , and p 6 Each of p is independently 0 or 1; 1 From 6 The photopolymerizable composition of claim 1 , wherein the sum of is a value from 3 to 6.
3. p 1 , p 2 , p 3 , p 4 , p 5 , and p 6 The photopolymerizable composition of claim 2 , wherein the sum of is a value of 4 to 5.
4. 2. The photopolymerizable composition of claim 1, wherein the highly crosslinkable acrylate monomer is ethoxylated pentaerythritol tetraacrylate.
5. Ethoxylated pentaerythritol tetraacrylate, and Unsaturated Polyester Oligomer The photopolymerizable composition of claim 1 or 2, comprising:
6. 6. The photopolymerizable composition of claim 5, wherein the weight ratio of the ethoxylated pentaerythritol tetraacrylate to the unsaturated polyester oligomer is from 0.2:0.8 to 0.8:0.
2.
7. The photopolymerizable composition of claim 6 further comprising a urethane acrylate oligomer.
8. 3. The photopolymerizable composition of claim 1, wherein the weight percentage of the ethoxylated pentaerythritol tetraacrylate is about 20% to about 60% by weight, the weight percentage of the unsaturated polyester oligomer is about 25% to about 75% by weight, and the weight percentage of the urethane acrylate oligomer is about 10% to about 50% by weight, based on the total weight of the ethoxylated pentaerythritol tetraacrylate and the oligomer combined.
9. 3. The photopolymerizable composition according to claim 1 or 2, wherein the weight ratio of ethoxylated pentaerythritol tetraacrylate to unsaturated polyester oligomer to urethane acrylate oligomer is 0.2:0.05:0.75 to 0.6:0.15:0.25, and preferably 0.4:0.1:0.
5.
10. 3. The photopolymerizable composition of claim 1, wherein the weight ratio of ethoxylated pentaerythritol tetraacrylate to unsaturated polyester oligomer to urethane acrylate oligomer is 0.4:0.1:0.
5.
11. 3. The photopolymerizable composition of claim 1, wherein the weight ratio of ethoxylated pentaerythritol tetraacrylate to unsaturated polyester oligomer to urethane acrylate oligomer is 0.3:0.3:0.
4.
12. 3. The photopolymerizable composition of claim 1 or 2, wherein the composition after photopolymerization has a heat deflection temperature of at least 100°C.
13. The photopolymerizable composition of claim 12, wherein the composition after photopolymerization has a heat deflection temperature of at least 150°C.
14. 14. The photopolymerizable composition of claim 13, wherein the composition after photopolymerization has a heat deflection temperature of at least 200°C.
15. A package comprising the composition of claim 1 or 2.
16. 13. A method for preparing a three-dimensional article, comprising applying one or more successive layers of the composition of claim 1 to produce a three-dimensional article, and exposing the successive layers to UV radiation.
17. 17. The method of claim 16, wherein said applying comprises depositing a first layer of said composition on a substrate and applying a second layer of said composition to said first layer, and optionally thereafter applying successive layers.
18. 17. The method of claim 16, wherein the three-dimensional article has a heat deflection temperature of at least 100°C.
19. 17. The method of claim 16, wherein the three-dimensional article has a heat deflection temperature of at least 150°C.
20. A three-dimensional article comprising successive UV-cured layers of the composition of claim 1.
21. 17. A three-dimensional article produced by the method of claim 16.
22. 22. The three-dimensional article of claim 20 or claim 21, wherein the three-dimensional article has a heat deflection temperature of at least 100°C.
23. 21. The three-dimensional article of claim 20, wherein the three-dimensional article has a heat deflection temperature of at least 150°C.
Citation Information
Patent Citations
Resin composition for 3D printing, antioxidant polymerization inhibition resin, 3D printing product and preparation method
CN111116833A
Method for manufacturing three-dimensional modeled object, and three-dimensional modeling device
WO2020162342A1